Magnesium isotopic evidence for chemical disequilibrium among cumulus minerals in layered mafic intrusion - Chen, Lie-Meng; Teng, Fang-Zhen; Song, Xie-Yan; Hu, Rui-Zhong; Yu, Song-Yue; Zhu, Dan; Kang, Jian (Earth and planetary science letters, 2018)
Magnesium isotopic compositions of olivine, clinopyroxene, and ilmenite from the Baima intrusion, SW China, for the first time, are investigated to constrain the magnitude and mechanisms of Mg isotope fractionation among cumulus minerals in layered mafic intrusions and to evaluate their geological implications. Olivine and clinopyroxene have limited Mg isotope variations, with δ26Mg ranging from −0.33 to +0.05‰ and from −0.29 to −0.13‰, respectively, similar to those of mantle xenolithic peridotites. By contrast, ilmenites display extremely large Mg isotopic variation, with δ26Mg ranging from −0.50 to +1.90‰. The large inter-mineral fractionations of Mg isotopes between ilmenite and silicates may reflect both equilibrium and kinetic processes. A few ilmenites have lighter Mg isotopic compositions than coexisting silicates and contain high MgO contents without compositional zoning, indicating equilibrium fractionation. The implication is that the light Mg isotopic compositions of lunar high-Ti basalts may result from an isotopically light source enriched in cumulate ilmenites. On the other hand, most ilmenites have heavy Mg isotopic compositions, coupled with high MgO concentration and chemical zoning, which can be quantitatively modeled by kinetic Mg isotope fractionations induced by subsolidus Mg–Fe exchange between ilmenite and ferromagnesian silicates during the cooling of the Baima intrusion. The extensive occurrence of kinetic Mg isotope fractionation in ilmenites implies the possibility of widespread compositional disequilibrium among igneous minerals in magma chambers. Consequently, disequilibrium effects need to be considered in studies of basaltic magma evolution, magma chamber processes, and magmatic Fe–Ti oxide ore genesis. •Large inter-mineral Mg isotope fractionation occurs in cumulus minerals.•Ilmenite displays the largest Mg isotopic variation among all igneous minerals reported so far.•Ilmenite has lower δ26Mg than coexisting clinopyroxene and olivine at equilibrium.•The isotopically heavy ilmenite is primarily produced by fast, subsolidus inter-mineral diffusion.•Chemical disequilibrium among minerals in layered mafic intrusions widely occurs.